Pelatihan Eco-Craft Untuk Pelestarian Lingkungan dan Pemberdayaan Perempuan Pesisir - Erma Suryani Sahabuddin; Rika Riwayani; Andi Makkasau; Muhammad Irfan; Hotimah Hotimah (INOVASI: Jurnal Hasil Pengabdian Masyarakat, 2026)
Abstract. Laikang District, with abundant marine resources, coastal communities, some of whom are Aisyiyah cadres in Laikang Village, whose economic background generally depends on marine products as their main source of income. However, facing a number of problems that hinder the existence of types of marine biota and by-products of marine activities, have not been fully utilized and only become waste that pollutes the coastal environment such as shells and fish scales. The solution is to implement a community service program (PKM) that focuses on utilizing marine biota waste through Eco-Craft Technical Training, Entrepreneurship Strengthening, Digital Marketing and Branding, Continuous Mentoring for Aisyiyah cadres. The method used is participatory-based service in every stage of research from planning to evaluation with data collection through surveys and questionnaires to understand the needs, problems, and potential that exist by the service team, and direct practice by the participants. This activity was attended by 10 participants who showed high enthusiasm during the training process. The evaluation results showed that participants had successfully mastered the Eco Craft making technique, and were able to produce products according to the standards taught. In addition to improving technical skills, this training also succeeded in fostering an understanding of the importance of Digital Marketing and Branding. The output of this PKM can raise the economic independence of Aisyiyah cadres and enrich the types of products from marine biota waste.Keywords: Eco-Craft, Coastal Women, Marine Waste, Economic Value Products